Sustained Remission With Atezolizumab in a Frail, Geriatric Patient With Advanced-Stage Large Cell Neuroendocrine Carcinoma Lung - Mayank Kapoor; Praneet Bedi; Deepak Sundriyal; Ashita Jain; Ujjawal Shriwastav; Amit Sehrawat (Case Reports in Oncological Medicine)
Large cell neuroendocrine carcinoma (LCNEC) is a rare, aggressive cancer primarily found in the lungs but can also occur in other organs. It is characterized by rapid progression and high metastatic potential. We present a case of advanced-stage LCNEC lung in a patient with a poor performance status (PS), requiring oxygen support. Imaging revealed a large right upper lobe mass, lymphadenopathy, with bronchial encasement and invasion into the superior vena cava, leading to SVC syndrome and pleural effusion. Biopsy and immunohistochemistry confirmed LCNEC. Due to the patient’s poor PS, treatment began with low-dose single-agent chemotherapy (carboplatin), followed by etoposide and cisplatin after improvement. Local radiation was also administered, and the treatment plan was adjusted to include atezolizumab. After 10 cycles, the patient achieved complete remission, sustained for 6 years. This case highlights the complexities of managing advanced LCNEC in a geriatric patient and the effectiveness of a multidisciplinary approach and immunotherapy.